Livelihood Strategies Shape Vulnerability of Households' Food Security to Climate in Senegal - Giannini, Alessandra; Ilboudo Nébié, Elisabeth Kago; Ba, Diaba; Ndiaye, Ousmane (Frontiers in Climate, 2021)
We integrate long-term observations of rainfall and repeat, large-scale, nationwide household surveys of nutrition and socio-economic status to assess the vulnerability of food security to climate in Senegal. We use a mixed methods approach and a vulnerability framework to explain how it is that food security is on average lower, and more variable year-to-year, in the climatologically wetter south and east of the country than in the drier western center and north. We find that it is sensitivity to climate that explains the spatial variation in food security, while exposure explains its temporal variation, but only where sensitivity is high. While households in the western center and north, geographically closer to the political and economic center of action, are less dependent on livelihoods based on climate-sensitive activities, notably agriculture, these activities still dominate in the more remote, landlocked and at times conflict-ridden south and east, where sensitivity to the vagaries of rainfall persists. As they work to strengthen the resilience of climate-sensitive activities, food security and climate-risk management projects and policies should move beyond simplistic, deterministic assumptions about how climate affects food security outcomes, and invest in livelihood diversification to increase rural income and reduce vulnerability of food security to climate.